Menyelaraskan spiritualitas dan profesionalisme : refleksi tasawuf dan wahdatul wujud dalam akuntansi syariah - tafziyah, salfa nurul (Maliki Interdisciplinary Journal, 2024)
This article examines the integration of Sufism values ​​in sharia accounting practice, with a focus on self-reflection and the concept of wahdatul wujud to build professional and spiritual awareness. Through reflection on Sufism, sharia accounting practices can be integrated with a deeper spiritual dimension. Conventional accounting tries to subdue human desires by creating a Code of Ethics for the Accounting Profession. The concept of the idea of ​​Wahdatul Wujud (unity of being) is the peak achievement and final form in Islamic society regarding philosophical Sufism. This article aims to explore how Sufism principles can enrich and strengthen sharia accounting practices, creating a synergy between spirituality and professionalism. The author’s suggestion is that it is important to provide education and training for sharia accounting practitioners so that they understand the application of the concepts of Sufism and Wahdatul Wujud in their work. This will help strengthen the integration of spiritual values ​​in their professional practice. Sharia accounting practices can continue to develop as an approach that not only meets financial demands, but also fosters spiritual values ​​that support prosperity and justice.